(untitled) - VESILIND, P. AARNE (USA, 1981)
1.Solid waste characteristics, production , and potential for resource recovery / 2.Historical background / 3.Materials flow in society / 4.Solid waste quantities and characteristics / 5.Potentials for reclamation of useful materials and energy from solid waste / 6.Obstacles to resource recovery / 7.Parting shots / 8.Collection of solid waste / 9.Solid waste collection systems / 10.Effectivenes of solid waste collection / 11.Collection of source - separated materials / 12.Litter / 13.Parting shots / 14.Storage , handling and shredding of solid waste / 15.Storage and conveying / 16.Compaction / 17.Shredding / 18.Pulping / 19.Roll crushing / 20.Parting shots / 21.Mechanical separation / 22.General expressions for materials separation / 23.Hand sporting / 24.Screens / 25.Air classifiers jigs / 26.Stoners / 27.Sink - Float separators / 28.Inclined tables / 29.Shaking tables / 30.Flotation / 31.Color sorting / 32.Parting shots / 33.Magnetic and electromechanical separation processes / 34.Magnetic separation / 35.Eddy current separation / 36.Electrostatic separation / 37.Magnetic fluids / 38.Parting shots / 39.Biochemical processes / 40.Methane generation by anaerobic digestion / 41.Methane generation in landfills / 42.Compositing / 43.Glucose production by acid enzymatic hydrolysis / 44.Other biochemical processes / 45.Parting shots / 46.Combustion / 47.Hitosrical background / 48.Principles of combustion / 49.Thermal balance in combustion / 50.Process variables / 51.Parting shots / 52.Incineration and energy recovery / 53.Incinerator desing concepts / 54.Other incineration process / 55.Waste heat recovery / 56.Air pollution control / 57.Parting shots / 58.Pyrolysis / 59.Process history / 60.Process characterization / 61.Process control variables / 62.Reactors / 63.Additional pyrolysis products / 64.Enviromental concerns / 65.Parting shots / 66.Ultimate disposal / 67.Options in ultimate disposal of residues / 68.Landfills / 69.Hazardous substances / 70.Parting shots
Incluye indice analitico pag.445